RESERVE ESTIMATION FOR AN AQUIFER-SUPPORTED RESERVOIR USING MATERIAL BALANCE (Journal of Engineering Studies and Research, 2023)
This study uses a straight-line material balance method to estimate the reserves of an undersaturated reservoir supported by an aquifer. Some computer algorithms to implement Van-Everdingen and Hurst models (VEHM) to calculate cumulative water influx were envisaged through the study's developed tool "QUANTIFY". The tool was then tested using published data. The Original Oil in Place (OOIP) for the given data was estimated to be 312.32 MMSTB with an R2 value of 0.99483. Subsequently, a comparative analysis was performed on the results obtained from MBAL and QUANTIFY, using Dake's result as a base/correct case. It was estimated that OOIP for QUANTIFY had a 0.1% error rate, while MBAL, a commercial software used to verify the result, had a 1.2% error rate. Invariably, the percentage errors were lower for the QUANTIFY software than for MBAL. The 3D plot of the reservoir energy drive from the "QUANTIFY" software, which was used to visualize the reservoir energy qualitatively, shows that the reservoir was mostly driven by water influx and fluid expansion. This study has demonstrated that "Water Influx" parameters can be computed appropriately without the use of charts or tables. The study has strengthened the validity of the Van Everdingen and Hurst aquifer model for reserve estimation for an aquifer-supported reservoir.
Keywords: reservoir, QUANTIFY, MBAL, simulation, water influx, undersaturated